RESEARCH THE IMPACT OF FDI ON SOME MACROECONOMIC INDICATORS IN BOSNIA AND HERZEGOVINA BY USING OF PROGRAM IBM SPSS STATISTICS - Šušić, Milan (Journal of process management and new technologies, 2018)
It is known that the economic stability and economic development of each economy depends on the free movement of capital. The international movement of capital has its balance of payment when capital export represents economic surplus in relation to consumption of the national economy and the import of capital represents an increase of consumption in regard to the output of a national economy. The paper is analyzed of the influence of foreign direct investment (FDI) on economic growth of the host country, among other things, is emphasized in the function of the achieved phase of its economic development. The aim of this paper refers to an attempt to indicate the significance and the role of FDI as well as the importance of attracting foreign direct investment in B&H and the determination of the effects of FDI on the economy of B&H. I am will try to prove it, ie to determine the degree of impact of FDI on some macroeconomic indicators in B&H (GDP, import, export, unemployment) by using IBM SPSS v.22 statistical analysis program (model) and applying the methods,calculating coefficients of correlation and regression analysis. In other words, i am will determine the analytical expression used to describe a statistical relationship of these macroeconomic categories.